ENERGY AND PROTEIN INGREDIENTS FOR USE IN PIAPARA (Megaleporinus obtusidens) DIETS: NUTRITIVE VALUE AND INTESTINAL MORPHOMETRY - Renata Akemi TANAKA; Viviane do Nascimento Santana de ALMEIDA; Carolina Vasconcelos Tavares de FARIAS; Luana Camargo SOUSA; Gabriela Castellani CARLI; Cleber Fernando Menegasso MANSANO; Leonardo Susumu TAKAHASHI (Boletim do Instituto de Pesca)
The apparent digestibility coefficients for crude protein (ADCCP), dry matter (ADCDM), and gross energy (ADCGE) of ingredients were determined for piapara (Megaleporinus obtusidens). Test diets were formulated to contain 69.5% of reference diet, 0.5% of chromium oxide, and 30% of test ingredients. The protein ingredients evaluated were tilapia processing residue meal (TPRM), feather and poultry blood meal (FPBM), poultry by-product meal (PBM), meat and bone meal (MBM), cottonseed meal (CM), corn gluten meal (CGM), and soybean meal (SM); the energy ingredients tested were corn (C), corn germ meal (CGRM), rice meal (RM), wheat bran (WB), and sorghum (S). Groups of 30 piaparas were fed twice daily during five days with test diets. Intestinal morphometry of fish were also evaluated. Digestibility coefficients of protein and energy ingredients were highest for soybean meal (ADCDM = 85.8%; ADCCP = 95.2%; and ADCGE = 87.2%) and corn (ADCDM = 94.5%; ADCCP = 76.2%; and ADCGE = 89.3%), respectively. Of the energy test ingredients analyzed, corn had the highest digestibility coefficients and induced beneficial changes on intestinal morphology compared to sorghum and corn germ meal. All protein ingredients showed potential for use in piapara diets, except meat and bone meal .